The evolution of flight - Glaeser, Georg; Paulus, Hannes F., 1943-; Nachtigall, Werner (Springer, 2017)
Discusses evolution's accomplishments in the world of flying: from the botanical air fleet (pollen grains, flying seeds ...), over flying snakes and fish, to penguins flying underwater and humans rising into the air. Mathematician and passionate animal photographer Georg Glaser has joined forces with the experienced evolutionary biologist Hannes Paulus and the exercise physiologist and flight biophysicist Werner Nachtigall in order to approach this topic with words and pictures in a way that is both generally comprehensible and scientifically sound. Double-page by double-page, the book can be read in any order. Cross-references allow to jump easily from one double-page to another. Aside from the detailed introduction to each chapter, the text passages are usually independent from one another, and they discuss crucial moments in the evolutionary process. The double-pages provide additional information on bibliographical references and references to informative websites.
Keywords: Animal flight.; Wings (Anatomy); Seeds -- Dispersal.; Pollination.; Evolution (Biology); elektronické knihy; electronic books